2012
DOI: 10.1364/oe.20.011407
|View full text |Cite
|
Sign up to set email alerts
|

Origin of thermal modal instabilities in large mode area fiber amplifiers

Abstract: We present a dynamic model of thermal modal instability in large mode area fiber amplifiers. This model allows the pump and signal optical intensity distributions to apply a time-varying heat load distribution within the fiber. This influences the temperature distribution that modifies the optical distributions through the thermo-optic effect thus creating a feedback loop that gives rise to time-dependent modal instability. We describe different regimes of operation for a representative fiber design. We find q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
121
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 268 publications
(133 citation statements)
references
References 10 publications
11
121
0
1
Order By: Relevance
“…Recent studies have also showed large dependency between TMI threshold and system parameters such as seed or pump noise as well as cooling conditions [6,19]. Seed noise can contain discrete frequency components possibly larger than the RIN, that if located within the frequency band of the nonlinear coupling constant reduces the TMI threshold.…”
Section: Estimating Modal Instability Thresholdmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies have also showed large dependency between TMI threshold and system parameters such as seed or pump noise as well as cooling conditions [6,19]. Seed noise can contain discrete frequency components possibly larger than the RIN, that if located within the frequency band of the nonlinear coupling constant reduces the TMI threshold.…”
Section: Estimating Modal Instability Thresholdmentioning
confidence: 99%
“…It is also assumed in the calculations that the density, heat capacity, thermal conductivity, and thermo-optic coefficient are temperature independent. In experiments, the absolute temperature of the fiber increases significantly at high output power [6] and depends on outer cooling properties, which can lead to variations in these coefficients.…”
Section: Estimating Modal Instability Thresholdmentioning
confidence: 99%
See 2 more Smart Citations
“…The results were interesting in the CCF due to thermal lensing that increases the cladding mode overlapping in the core region. Furthermore, one can name other thermal effects such as thermally induced phase mismatching [14], thermal modal instability [15], and depolarization loss [16].…”
Section: Temperature Distributionmentioning
confidence: 99%